BRCA and Pancreatic Cancer: Selection of Chemotherapy - Kim, Richard; Byer, Jenifer; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2012)
Germline mutations in BRCA genes are associated with increased risk of pancreatic cancer. There are pre clinical data which suggests that DNA cross linking agents should be used in pancreatic cancer patients with BRCA mutations. This review is an update from the 2012 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium regarding recent developments in the treatment of pancreatic cancer with BRCA mutation. Only one study (Abstracts #217) was presented and it is described here.